Implementasi Modul Ajar di Sekolah SMPN 12 Palangka Raya dalam Mata Pelajaran PAK Kelas VII SMP FASE D - Nafaya Yesilia; Liska Meri Monika; Fitri Fitri; Matius Timan Herdi Ginting (Nubuat : Jurnal Pendidikan Agama Kristen dan Katolik, 2025)
This study aims to describe the implementation process of the Christian Religious Education teaching module with the topic "Human Life in God's Care" for seventh-grade students of SMP Negeri 12 Palangka Raya. The focus of the activity was directed to determine the implementation of learning, student responses, and learning outcomes achieved through the biblical story approach, discussion, reflection, and creative poster-making projects. The research method used was descriptive qualitative with data collection techniques through observation, documentation, and assessment of work results. Data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results showed that the implementation of the teaching module went well and achieved the learning objectives. Students were able to understand the concept of God's care, relate God's word to personal life experiences, and demonstrate an attitude of gratitude through reflection and discussion. In addition, students produced a poster with the theme "God Cares for My Life" as a form of creative expression and the meaning of faith. Despite several obstacles such as limited time for the project and variations in student activity levels, learning remained effective and conducive. The assessment showed positive developments in the cognitive, affective, and psychomotor aspects of students.